Low cycle fatigue behaviour of modified and conventional superalloy Inconel 718 at 650°C - Krishna E.H.; Prasad K.; Kumar V.; Singh V. (My University, 2025)
The present investigation deals with the study and comparison of low cycle fatigue (LCF) behavior of modified IN 718 alloy with higher Al+Ti/Nb and Al/Ti ratios of 0.458 and 0.870, with that of conventional IN 718 alloy with corresponding ratios of 0.294 and 0.50 respectively. LCF tests were carried out in total strain control mode at total strain amplitudes (Δε t/2) from ±0.625% to ±1.0%, in fully reversed loading (R= -1) at 650°C. The modified alloy was found to exhibit better LCF resistance than the conventional alloy. © 2010 Indian Institute of Metals.